Analysis of the Main Character's Inner Conflict in the Novel "Milea Suara Dari Dilan" by Pidi Baiq - Kurnia Kurnia; Nur Hafsah Yunus; Sudirman Sudirman (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
This study aims to describe the forms of inner conflict, the causes of inner conflict, and the form of resolution of the main character's inner conflict in the novel “Milea Suara Dari Dilan” by Pidi Baiq. This type of research is descriptive qualitative where the data is in the form of written words or descriptions. Based on the results of the study it can be concluded that the form of inner conflict experienced by the main character includes disputes between choices that are not in accordance with desires, confusion in experiencing problems and desires that are not in accordance with reality. The cause of the main character's inner conflict consists of two causes, namely external and internal causes. The forms of solving the inner conflict of the main character in the novel are sublimation, repression, rationalization, and projection.